Web-based intervention to improve the evidence-practice gap in minimal intervention dentistry: Findings from a dental practice-based research network. (December 2021) - Kakudate, Naoki; Yokoyama, Yoko; Sumida, Futoshi; Matsumoto, Yuki; Takata, Tomoka; Gordan, Valeria V.; Gilbert, Gregg H.
Abstract: Objectives: To determine whether: the evidence-practice gap (EPG) in minimal intervention dentistry (MID) can be improved by a tailored web-based intervention, and specific clinical situations might impede implementing MID. Methods: We conducted a before-after intervention study and a qualitative study. Two web-based questionnaire surveys were conducted among 197 Japanese dentists. In the first questionnaire, a baseline EPG was measured using six questionnaire items. Subsequently, feedback material about the EPG was electronically prepared, including results of the first questionnaire, international comparisons with a previous study from the US, and a summary of recent evidence on MID. In the second questionnaire, the EPG was re-measured after participants read the material. The primary outcome was mean overall concordance between published evidence and the dentist's clinical practice for all six questions. During the second questionnaire, we performed qualitative content analysis using free-text responses to a question about difficult situations encountered when conducting MID. Results: Regarding before and after comparisons of concordance between the first and second questionnaires, mean overall concordance improved significantly, from 66% to 89% ( p <0.001). Qualitative content analysis identified five difficult situations: "cases where decision making for treatment and prognosis is difficult", "inadequate practice resources", "limitations on patient visit and treatment period", "discrepancy between MID and the patient's values", and "limitations on health insurance and social understanding". Conclusions: These results suggest that it is possible to reduce the EPG in MID using a web-based educational intervention among Japanese dentists. Qualitative content analysis revealed five difficult situations that might hinder implementation of MID. Clinical Significance: Although this intervention demonstrated educational effects, perfect concordance was not achieved by all participants. This is possibly associated with the five situations that participants reported facing when conducting MID. Creating an environment to improve these situations may facilitate a reduction in the EPG.